Millennial Employee Turnover: Contributive Factors and Retention Strategies in the Indonesian Industry - Ratnasari, Dian; Octafian, Ray (MultiTech Publisher, 2024)
This research aims to explore the phenomenon of millennial employee turnover in the Indonesian industry, identify the contributive factors to the high turnover rate, and formulate effective retention strategies to retain millennial talent. The research method used is a qualitative approach with data collection techniques through semi-structured interviews and participatory observation. The participants in this study are 6 millennial employees, 1 supervisor, and 1 manager from one of the industries in Indonesia, selected through purposive sampling. The results of the study show significant differences in values and work culture between the millennial generation and previous generations. Millennials tend to desire a more flexible, collaborative work environment that focuses on individual development. They also have higher expectations regarding technology, innovation, and more frequent feedback and recognition. These differences can pose challenges in intergenerational communication and collaboration in the workplace. The implications of this research include the need for transformation in HR management practices to accommodate the characteristics and expectations of millennial employees. Companies that successfully adapt their HR management approach will be better able to attract, retain, and optimize the potential of millennial talent, thereby driving business growth and innovation in this increasingly competitive era